The Veterinary Clinical Skills Laboratory Initiative - Sarah Baillie; Emma Crowther; Marc Dilly (Universitat Politècnica de València, 2015)
Veterinary students need to develop competence in clinical skills in preparation for working in practice. Models and simulators are increasingly used to help supplement existing training and are often housed in a clinical skills laboratory. The laboratory provides a safe environment where students can practise repeatedly on models in order to develop proficiency. It is also an ideal venue to run practical classes and assessments, such as an objective structured clinical examination (OSCE). The veterinary clinical skills laboratory initiative is relatively new and recent growth and has been facilitated by several factors. There is much that can be learned from medical education and other health professions as their clinical skills laboratories have been running for many years. Additionally, there are several veterinary conferences that now include dedicated clinical skills sessions and have workshops where, for example, delegates can share tips about making models and discuss developing and managing laboratories. To complement face-to-face meetings, there is a thriving international community, the Veterinary Clinical Skills & Simulation group, in the online forum NOVICE (Network Of Veterinarians In Continuing Education). Members ask questions, usually receiving rapid responses, share tips and collate useful information. Recently a free guidebook to clinical skills laboratories has been written by an international collaboration and provides key information for those setting up laboratories or extending existing facilities. There can be little doubt that the veterinary clinical skills initiative will continue to grow and share expertise with associated benefits for student learning and animal welfare.